Impact of COVID-19 pandemic on household consumption pattern of dairy products in India - Bhandari, Gunjan; Lal, Priyanka; Kumari, Binita (Indian Journal of Dairy Science, 2023)
Besides other things, the effect of COVID-19 pandemic is evident in income and consumption pattern of the households. Income loss, fear of infection and movement restrictions has not only altered the amount and pattern of spending but has also changed the shopping behaviour of the consumers. In the case of food commodities, dairy products seem to be more susceptible to such changes owing to their perishability and comparatively higher income elasticity. But, contrary to this expectation, there were speculations that household dairy consumption in India might have increased during lockdown due to more number of meals at home and immunity boosting qualities of milk. Any change in dairy consumption in India has a direct bearing on household nutritional security as it acts as a major source of protein for a large proportion of population. Â Thus, the present study attempts to capture the impact of COVID-19 pandemic on household consumption pattern of dairy products across geographical regions, household locations and income class on the basis of a pan-India survey covering around 1000 households. The results revealed that there was a significant decline in the household consumption of milk, paneer, butter and ice-cream during lockdown whereas no significant change was observed in the consumption of ghee, curd and buttermilk. The fall in demand was comparatively higher in the urban households, milk deficit zones and among the lowest income class. Moreover, a shift was also observed towards packaged products and online delivery services.